Ecological aspects of Chironomidae larvae (Diptera) of the Opia river (Tolima, Colombia). (2018)
A study of the taxonomy and ecological aspects of Chironomidae (Diptera) in the Opia river, (Tolima, Colombia) was conducted in order to determine the faunal composition of this area and its relation to environment factors. Sampling stations were selected according to the status of the various sections of the river, access areas and intensity of human impacts. Aquatic macroinvertebrates were collected from nineteen stations and the main characteristics of each station were recorded, temperature and conductivity variables were measured in situ, and water samples were taken at fourteen stations for the analysis of fifteen physicochemical parameters. In this study, 4,389 Chironomidae larvae were collected, which were comprised of 75.71 % Chironominae; 16.86 % Orthocladiinae and 7.43 % Tanypodinae. From these samples, sixteen genera are reported for Tolima and the environmental conditions (substrate, riparian vegetation, water quality and velocity) for each genus are presented. The results showed that genera Rheotanytarsus, Polypedilum, Thienemanniella, Corynoneura and Pentaneura can be considered to be resistant to environmental impacts on the Opia river.